2021
DOI: 10.4314/ahs.v21i2.31
|View full text |Cite
|
Sign up to set email alerts
|

Circulatory microRNA expression profile for coronary artery calcification in chronic kidney disease patients

Abstract: Background & Aim: Coronary artery disease (CAD) is the primary cause of mortality in patients with end stage renal disease (ESRD). MicroRNA profiling is proven as a powerful tool in the diagnosis of any disease at the molecular level. Hence, the present study aimed to profile the microRNA expression for CAD especially coronary artery calcification in CKD patients. Materials and Methods: Two hundread patients with CKD stages 3 to 5 without dialysis and healthy controls were includ- ed in this study. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Calcification of atherosclerotic plaques is secondary to the development of coronary artery disease. Early detection of coronary calcification is an important marker for early diagnosis [19][20][21][22][23][24]. MicroRNA is a factor related to the formation of atherosclerosis that has been concerned in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Calcification of atherosclerotic plaques is secondary to the development of coronary artery disease. Early detection of coronary calcification is an important marker for early diagnosis [19][20][21][22][23][24]. MicroRNA is a factor related to the formation of atherosclerosis that has been concerned in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Chao et al [25] discovered that serum miR-125b2-3p and miR-378a-3p levels decreased with increasing severity of VC in 155 CKD patients. Another study demonstrated that the serum levels of 13 miRNAs (up-regulated: miR-21, miR-67, miR-390, miR-56, miR-250, miR-65, miR-13; down-regulated: miR-235, miR-256, miR-226, miR-207, miR255, miR193) differed signi cantly in seven CKD patients compared with control patients [26]. Because of the complex situations in patients, the characteristics of circulating miRNAs and exosome cargo miRNAs may differ.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA are able to exert an array of biological func tions, including: (1) regulation of DNA transcription by acting with a transcription facto (2) epigenetic silencing and repressing the histone modification via chromatin interaction (3) mRNA translation (4) post-translational regulation through miRNA sponges o circRNA, (5) scaffold of protein complex, (6) shorter ncRNAs (siRNA) generation (Figur 1B). Noncoding RNAs are largely involved in cardiovascular physiology, atherosclerosi [35], and multiple cardiovascular diseases [36], as chronic and acute coronary syndrome [6,[37][38][39][40][41], vascular remodeling [29,42], valvular heart disease [43][44][45][46][47], generation and pro gression of ectopic calcifications in the cardiovascular system [48][49][50][51][52][53][54], platelet functio [55][56][57][58][59], heart failure and stroke [60][61][62][63][64][65][66][67][68][69][70]. Evidence of the impact of flow conditions on cir culating ncRNA derives both from observations on pathological changes, such as cardia valve disease, vascular stenoses or aneurysm, but also from physiological conditions, suc as exercise [68].…”
Section: Noncoding Rnasmentioning
confidence: 99%
“…This review focuses on regulatory noncoding RNAs that are directly or indirectl responsive to flow and their involvement with cardiovascular effects of altered bloo flow, with a focus on the potential clinical relevance and the underlying molecular mech anisms and their possible use as clinical biomarkers [71]. As relevant evidence is no equally available for all ncRNAs sub-categories, some specific ncRNAs, including siR NAs, snoRNA or piRNA are not mentioned in this review due to lack of evidence in rela Noncoding RNAs are largely involved in cardiovascular physiology, atherosclerosis [35], and multiple cardiovascular diseases [36], as chronic and acute coronary syndromes [6,[37][38][39][40][41], vascular remodeling [29,42], valvular heart disease [43][44][45][46][47], generation and progression of ectopic calcifications in the cardiovascular system [48][49][50][51][52][53][54], platelet function [55][56][57][58][59], heart failure and stroke [60][61][62][63][64][65][66][67][68][69][70]. Evidence of the impact of flow conditions on circulating ncRNA derives both from observations on pathological changes, such as cardiac valve disease, vascular stenoses or aneurysm, but also from physiological conditions, such as exercise…”
Section: Noncoding Rnasmentioning
confidence: 99%